Impact of Genetic Polymorphisms at the Promoter area of IL-10 Gene on Tacrolimus Level in Jordanian Renal Transplantation Recipients - Khaleel, Bara’ah; Yousef, Al-Motassem; AL-Zoubi, Mazhar; AL-Ulemat, Muhammad; Masadeh, Ahmad; Abuhaliema, Ali; AL-Batayneh, Khalid; Al-Trad, Bahaa (Journal of Medical Biochemistry, 2021)
BackgroundTacrolimus is a widely used immunosuppressant that prevents the solid organ transplant rejection. The pharmacokinetics of Tacrolimus show considerable variability. interleukin-10 (IL-10), in the host’s immune response after transplantation contributes to the variable CYP3A-dependent drug disposition of Tacrolimus. In current study, our aim is to evaluate the impact of single nucleotide polymorphisms (SNP) in the promoter region of of IL-10 on Tacrolimus dose requirements and the Dose Adjusted Concentration (DAC) of Tacrolimus among kidney transplantation recipients. MethodsBlood levels of Tacrolimus were measured using Micorparticle Enzyme Immunoassay (MEIA) for six months post-transplantation. Genotyping analysis was utilized using specific Polymerase Chain Reaction (PCR) followed by sequencing methods for 98 Jordanian kidney transplant recipients.ResultsGenotyping frequencies of IL-10 (-592) were (CC/CA/AA: 38, 46.7, 15.2%); IL-10 (-819) were (CC/CT/TT: 40.4, 44.1, 15.1%); and IL-10 (-1082) were (AA/AG/GG: 42.6, 44.7, 12.8%). The impact of IL-10 (-1082) on Tacrolimus DAC was gender dependent. Men carrying at least one A allele had significantly lower DAC than men carrying GG genotyping only in the first month post-transplantation [88.2±32.1 vs. 117.5±22.5 ng/ml per mg/kg/day, p=0.04]..ConclusionOur current study showed that the interaction between gender and IL-10 -1082 affects Tacrolimus DAC in Jordanian kidney transplantation recipients during the first month post-transplantation.
Keywords: IL-10 genetic polymorphism; Kidney Transplantation; Pharmacokinetics; Tacrolimus.